Upper fourth at Malory towers - Blyton, Enid. (b)
Fourth in the series. Darrell has an exciting term in store. Not only does her sister Felicity start at Malory Towers, she's made Head of the Fourth year! But can Darrell live up to the responsibility of the role?
Keywords: Malory Towers (Imaginary place) -- Juvenile fiction; Boarding schools -- Juvenile fiction; Boarding schools